Família, compadrio e relações de poder no Marajó (séculos XVIII e XIX) - Soares, Eliane Cristina Lopes (2010)
This paper aims to discuss the importance of the family and crony in the constitution of the marajoara society, emphasizing the networks of relationships that gave rise. In the formation of the colonial society and its subsequent consolidation settled solidarities and tensions around the issue of access to land, obtaining favors public office, the struggles for labor force, among other situations, which had as central element the favoring of the family groups or their next of kin. Understand the importance of these networks is essential, as are the bases of policy positions and economic that created a safety net and tried to benefit or to favor relatives, kin or spiritual. In small uprisings, insubordinations or simply opening a will perceive the relationship influencing decisions and behaviors. Care about the entities was expressed even when they were not legally constituted, especially in the final moments of life of the individual who has at last acknowledged in their wills or letters of affiliation. The feeling of belonging to this or that family often contributed to the applicant's choice of godfathers of certain families, which created, in turn, a host of kindred that increased the minimum, the status of a particular individual in the local social group. Not always have many godchildren and cronies can accounted for, if we might just as policy-making, however, the societies of the eighteenth and nineteenth centuries, the symbol of power was also associated with social status, visibility among others. The expansion of the family, through marriage or sponsorship system means having to turn to, even if not economically or politically, but simply as an ally and kinsman